Development of ATAQ-LAM: a tool to assess quality of life in Lymphangioleiomyomatosis - Walker, Tarik D. (Health Qual Life Outcomes, 2015)
BACKGROUND: Lymphangioleiomyomatosis (LAM) is a progressive lung disease that impairs health-related quality of life (HRQL). OBJECTIVE: To develop and conduct initial testing of ATAQ-LAM (A Tool to Assess Quality of Life in LAM). METHODS: A pilot version of the questionnaire was administered to respondents with LAM. We used a deletion algorithm to retain items and then applied multi-trait scaling to place retained items into appropriate domains, thus generating the ATAQ-LAM. Rasch analysis was used to assess item fit to a unidimensional model of HRQL. We determined internal consistency (IC) and floor and ceiling effects of ATAQ-LAM scores and conducted analyses aimed at supporting the validity of ATAQ-LAM. RESULTS: Sixty-nine LAM patients provided response data. Thirty-two items survived the deletion algorithm. Scaling suggested ATAQ-LAM should have a four-domain structure (Exertional dyspnea, IC = 0.94; Cough, IC = 0.91; Fatigue, IC = 0.91; Emotional Well-Being, IC = 0.89). All items fit the Rasch model. Among 17 respondents with spirometry within three months of questionnaire completion, three of five ATAQ-LAM scores correlated with FEV1% (Exertional Dyspnea: r = −0.72, p = 0.001; Fatigue: r = −0.62, p = 0.007 and total: r = −0.53, p = 0.02). Compared with those in the highest tertile of FEV1%, subjects in the lowest tertile had greater ATAQ-LAM total (121.8 ± 14.3 vs. 79.8 ± 13.1, p = 0.04), Exertional Dyspnea (54.4 ± 6.3 vs. 25.5 ± 5.8, p = 0.005) and Fatigue (2.8 ± 2.4 vs. 14.8 ± 2.3, p = 0.03) scores, indicating greater impairment in HRQL. CONCLUSIONS: ATAQ-LAM is a disease-specific instrument designed to assess HRQL in LAM patients. Additional studies are needed to generate data in support of its validity as an instrument capable of assessing HRQL over time in LAM patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12955-015-0294-5) contains supplementary material, which is available to authorized users.